The Management Of Inclusion Class Learning (A Site Study at SDN Kaliboto Purworejo) - Suherman, Suherman; , Prof. Dr. Sutama, M.Pd; , Dr. Phil Dewi Candraningrum, M.Ed (2013)
There were three purposes of this study. The first was to describe the preparation of inclusion class learning at SDN Kaliboto Purworejo. The second was to know the relationship between students with special needs and normal students on inclusion class learning at SDN Kaliboto Purworejo. And finally, this study described the evaluation of inclusion class learning at SDN Kaliboto Purworejo. It was a qualitative research by using ethnography design. The main subjects included the principal, teachers and students. Data collection method used interview, observation, and documentation. Data analysis was started by the data reduction, data display, and drawing conclusion. Data validity test used triangulation technique. The findings suggested that learning of inclusion class at SDN Kaliboto Purworejo was well-prepared. The preparation included training to improve teachers' competencies who did not all have the psychologist educational background. The training given was able to increase teachers' competence in preparing the needs of learning. Teachers were able to prepare documents for any study, including preparing documents the developmental analysis of students with special need. The preparation done included the preparation of instructional materials, aids and instructional media. At first, communication and social relationships between students with special needs and normal students have problems. Students with special needs felt insecure and less confident, as well as normal students who think them different. Responding to this, teachers conducted individual approach to each student so that a harmonious relationship happened in inclusion learning. Students with special needs were not shy to ask and share stationery, while normal students helped their difficulties by being peer tutors. Evaluation for inclusion class learning in SDN Kaliboto Purworejo is done every day. Teachers used a lower standard score and the difficulty level of questions than the normal students. Teachers used written, oral, and practice evaluations to determine the development of students with special need in particular the development of cognitive, affective, and psychomotor aspects. There was a dispensation of time for finishing the questions, and the questions were also translated to Braille letters for the students who have visual impairment. The results of the evaluation in one year were made in the report books that contained the score achieved by students and the qualitative description of students' skill.